2017
DOI: 10.1186/s12879-016-2132-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between a syndemic of psychosocial problems and unprotected anal intercourse among men who have sex with men in Shanghai, China

Abstract: BackgroundPrevious studies have discussed the overlapping and reinforcing effects (defined as a syndemic) of psychosocial problems on high-risk sexual behaviors among men who have sex with men (MSM). The present study aimed to apply the syndemic theory to verify the reinforcing effects of psychosocial problems on unprotected anal intercourse (UAI) among MSM in Shanghai, and determine if other important psychosocial factors fit into the syndemic theory.MethodsData were collected from 547 MSM in Shanghai, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
(70 reference statements)
2
24
1
Order By: Relevance
“…The CES-D scale [23] is usually used as a screening tool in clinical practice and has high sensitivity, which may have led to the higher depression prevalence found in our study. In studies carried in Shanghai and west China, 52.1% and 50.8% had depression symptoms [2,24], which is higher than the results in our study; despite adopting the same depression scale, these discrepancies might be due to differences in culture and HIV infection status.…”
Section: Discussioncontrasting
confidence: 92%
“…The CES-D scale [23] is usually used as a screening tool in clinical practice and has high sensitivity, which may have led to the higher depression prevalence found in our study. In studies carried in Shanghai and west China, 52.1% and 50.8% had depression symptoms [2,24], which is higher than the results in our study; despite adopting the same depression scale, these discrepancies might be due to differences in culture and HIV infection status.…”
Section: Discussioncontrasting
confidence: 92%
“…Respondents that identified as MSM and had an income above 10,000 Nepalese rupees had a lower likelihood of using a condom in the last sexual encounter compared to respondents that earned less. Studies have shown both low and high income to be associated with more unprotected sex and the underlying reason behind the observed association is not clear [32][33][34]. Controlling for the other covariates in the model, being forced by family to marry a female was associated with lack of condom use during the last sexual encounter among MSM.…”
Section: Individual and Socio-structural Factors Associated With Sexumentioning
confidence: 86%
“…Since Singer et al (7), first described the syndemic theory, a growing number of studies have utilized this framework to understand HIV sexual risks in diverse populations in North America (3942), Asia (43) and now emerging in sub-Saharan Africa (9,44). Here we extend the syndemic framework to young men residing in an informal township setting in Cape Town, South Africa.…”
Section: Discussionmentioning
confidence: 99%